Evaluating housing in urban planning using TOPSIS technique: cities of Isfahan province - Izadi Maliheh; Vardanjani Mehdi Jafari; Varesi Hamidreza (Bulletin of Geography. Socio-Economic Series, 2021)
The indices of housing serve as an important tool in planning for housing, in that they allow the parameters affecting housing to be recognised and any planning process to be facilitated. The purpose of the study is to investigate and to evaluate the housing situation in cities of Isfahan province. The study is applied and descriptive-analytic in terms of method. Thirty-nine indices were collected in the housing sector. Then the rate of prosperity and ranking of the cities were evaluated by TOPSIS method. Prosperity is defined here as an important index of housing that reflects the welfare of residents. The cities were then categorised into six levels of prosperity: Very important, Important, Partially important, Moderate, Poor and Very poor. The results from the study indicate an imbalance in the studied indices between the cities, and a clear disparity between the levels of prosperity in the cities, and the only city in the very prosperous group is Isfahan, with a rate of 0.813.